Ultrasonic obstacle detection of a hexarotor unmanned aerial vehicle - Chua, Harrold Hao-Ru (2016)
Achieving fully autonomous UAV flight system incorporates many different technologies and instruments (i.e. obstacle detection, path planning, on-board control, navigation, vision systems) to synergise with each other. This project focuses on the obstacle detection aspect, namely ultrasonic sensing technology. The advantages and disadvantages will be explored and experimented upon, all while using the Raspberry Pi 2 (a card-sized single board computer newly developed with the intent of promoting computer science) to handle the flight sensing and control. Ultrasound capabilities will be monitored to identify the ideal sensor model and determine if it is capable to be utilized and integrated with autonomous flight. On top of that, methods of display, storage and utilization of obstacle detection data is expanded upon as well.